Preparação e caracterização de catalisadores à base de titânio suportado em MCM-41 para produção de compostos oxigenados através da pirólise catalítica do capim elefante - Fontes, Maria do Socorro Braga (2013)
In recent years, the area of advanced materials has been considerably, especially when it comes to materials for industrial use, such as is the case with structured porosity of catalysts suitable for catalytic processes. The use of catalysts combined with the fast pyrolysis process is an alternative to the oxygenate production of high added value, because, in addition to increasing the yield and quality of products, allows you to manipulate the selectivity to a product of interest, and therefore allows greater control over the characteristics of the final product. Based on these arguments, in this work were prepared titanium catalysts supported on MCM-41 for use in catalytic pyrolysis of biomass, called elephant grass. The reactions of pyrolysis of biomass were performed in a micro pyrolyzer, Py-5200, coupled to GC / MS, the company CDS Corporation, headquartered in the United States. The catalysts Ti-MCM-41 in different molar ratios were characterized by XRD, TG / DTG, FT-IR, SEM, XRF, UV-visible adsorption of nitrogen and the distribution of particle diameter and specific surface area measurement by the BET method. From the catalytic tests it was observed that the catalysts synthesized showed good results for the pyrolysis reaction.The main products were obtained a higher yield of aldehydes, ketones and furan. It was observed that the best reactivity is a direct function of the ratio Si/Ti, nature and concentration of the active species on mesoporous supports. Among the catalysts Ti-MCM-41 (molar ratio Si / Ti = 25 and 50), the ratio Si / Ti = 25 (400 ° C and 600 ° C) favored the cracking of oxygenates such as acids , aldehydes, ketones, furans and esters. Already the sample ratio Si / Ti = 50 had the highest yield of aromatic oxygenates